A worldwide bibliometric analysis of Antarctic krill research during 1960 to 2015. Issue 4 (2nd October 2017) - Liu, Fei
ABSTRACT: This study conducted a bibliometric analysis of 1251 articles related to Antarctic krill from 1960 to 2015, based on the Core Collection in Thomson Reuters' Web of Science. We analyzed the results from four aspects: annual distribution, Web of Science categories and the major journals, international collaboration and author keywords. The Antarctic krill research has developed rapidly since 1978, with an increasing article output. The studies mostly focused on the fields of marine and freshwater biology, oceanography, and ecology. Polar Biology, Marine Ecology-Progress Series and Deep-Sea Research Part II-Topical Studies in Oceanography, were the top three journals to publish the Antarctic krill-related papers. Although Russia is the earliest state to report Antarctic krill, U.S.A. and England were leaders with the largest output quantity and the highest cooperation frequencies. The researches in PR China have taken a blooming since 2009 and will play a more and more important role in the world. The frequencies of author keywords were counted. The high-frequency keywords were further divided into four groups with cohesive subgroup analysis, which suggested the major themes. This paper depicts the existing publications on Antarctic krill. Our goal is to serve a point of reference and provide the direction for the future work.